Energy from biomass: alternative for the reduction of atmospheric emissions - Galvis Martinez, John Freddy; Torrado Gómez, Luz Marina; Serrano Guzmán, Maria Fernanda; Solarte Vanegas, Norma Cristina; Perez Ruiz, Diego Dario (Lámpsakos (revista descontinuada), 2020)
Biomass produces the same amount of emissions of carbon dioxide absorbed during its growth that means that emits the same amount of CO2 processing during part of its life cycle, making it neutral emissions of carbon compounds. The mass use of this energy source in developing countries with high agricultural potential is not considered feasible. This article from a research project describes the processes for biomass utilization and environmental benefits of using this energy resource that has been booming in different countries. It is concluded that although it is feasible the inclusion of biomass for energy supply, exists a lack of guidelines for sustainable use.